Engineering a probiotic Bacillus subtilis for acetaldehyde removal: A hag locus integration to robustly express acetaldehyde dehydrogenase. - Chandler Hassan-Casarez; Valerie Ryan; Bentley M Shuster; John W K Oliver; Zachary D Abbott (PLoS ONE)
We have addressed critical challenges in probiotic design to develop a commercially viable bacterial strain capable of removing the intestinal toxin, acetaldehyde. In this study, we report the engineering of the hag locus, a σD-dependent flagellin expression site, as a stable location for robust enzyme production. We demonstrate constitutive gene expression in relevant conditions driven by the endogenous hag promoter, following a deletion of the gene encoding a post-translational regulator of σD, FlgM, and a point mutation to abrogate the binding of the translational inhibitor CsrA. Reporter constructs demonstrate activity at the hag locus after germination, with a steady increase in heterologous expression throughout outgrowth and vegetative growth. To evaluate the chassis as a spore-based probiotic solution, we identified the physiologically relevant ethanol metabolic pathway and the subsequent accumulation of gut-derived acetaldehyde following alcohol consumption. We integrated a Cupriavidus necator aldehyde dehydrogenase gene (acoD) into the hag locus under the control of the flagellin promoter and observed a rapid reduction in acetaldehyde levels in gut-simulated conditions post-germination. This work demonstrates a promising approach for the development of genetically engineered spore-based probiotics.